Corporate Strategic Response to globalization: an Empirical Study - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
The globalization of competition has recently led many firms to integrate their information systems. Based on a selective review of literature on strategic and information management, a model is developed to study corporate strategic response to the APEC Free Trade Agreement (AFTA). The purpose of this study is to investigate the impact of competitive strategy, information technology maturity and size on a firm's strategic response to AFTA. A survey of 44 firms found that information technology development influences the perceived increase in a firm's investment in information technology. Competitive strategy and size do not affect afirm' s strategic response to perceived increase in investment in information technology. This suggests that new increasing, competitive strategies will consist of technology-based global initiatives that are affected by the firm's level of development in information technology.